EFEKTIFITAS MEDIA BECAK DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN KETRAMPILAN BERFIKIR KRITIS SISWA SD/MI - Widiana, Galuh Tisna; Ulum, Maufuzul; Nurrrohmah, Triya; Arobi, Achmad Zainul Hasan (JURNAL PENDIDIKAN DASAR NUSANTARA, 2018)
“Becak” is one of three dimensional visual media that can be concrete the student’s understanding towards the material of transplantation. Because of becak media, student’s can see participate. Student’s will be easy to understand the material because it’s practical and should be visualized. The aim of this media is student’s can practice “Becak” (Belajar Cangkok) media in the IPA learning. It’s to develop the critical thinking skills of student’s elementary school. This research uses experiental method and research variabel uses pre-test and post-test. By using this method, the researcher will know the understanding from each student. How the apply the media correctly. By the concrete media and the participation of students’s the learning process will be impressive. So that the student’s understanding will grow on their own in the way they participate in the learning process. Keywords: effectiveness, media, critical.